P12 TLR8 agonist VTX-2337 sensitizes head and neck cancer cells to cetuximab. Issue 5 (May 2015) - Lei, Y.; Cong, L.; Kansy, B.; Ferris, R.L.
Abstract : Background: Autophagy is an evolutionarily conserved process in eukaryotic cells to recycle damaged organelles, protein aggregates, and misfolded proteins, providing an efficient adaptive mechanism against inflicting environmental challenges, such as nutrient deprivation, hypoxia, and fluctuation in growth factor availability. Dysregulation of autophagy is an emerging mechanism of cancer cell resistance to treatment. Priming of TLR8 in peripheral blood monocytes with a small molecule pharmacologic agonist VTX-2337 has been recently shown to potently augment cetuximab-induced natural killer (NK) cell-mediated cytotoxicity in head and neck cancer (HNC) cells. In this study, we exploited the potential of VTX-2337 in modulating cancer cell autophagy and its effect on directly sensitizing cancer cells to cetuximab treatment in vitro. Materials and methods: PCI-13 and UDSCC2 HNC cells were treated with 1.0  μ M VTX-2337 for 5 h, and cell lysates were harvested for immunoblotting analysis of LC3B. Densitometry was performed to calculate the ratio of LC3B-II/ β -actin to assess autophagy induction. LC3B-GFP expression was induced in PCI-13 cells for confocal imaging analysis. The inhibitory effects of VTX-2337 on HNC cell proliferation and its ability of sensitizing cancer cells to cetuximab were measured by XTT cell proliferation assay. Results: TLR8 was variably expressed in both PCI-13 and UDSCC2 HNC cells. Treatment of VTX-2337 at 1.0  μ M for 5 h potently induced autophagy, shown by the increased ratio of LC3B-II/ β -actin density. Blockade of the degradation of LC3B-II with a pharmacologic inhibitor chloroquine did not abrogate VTX-2337-induced upregulation of the LC3B-II/ β -actin ratio, suggesting VTX-2337 promoted autophagic flow instead of non-specifically inhibiting the degradation of LC3B-II. Confocal imaging showed increased LC3B-GFP puncta upon VTX-2337 treatment. Although cetuximab treatment alone had little effect on cell proliferation, a combination with VTX-2337 substantially sensitized PCI-13 and UDSCC2 cells to cetuximab, and inhibited cancer cell proliferation quantitated by XTT assay. Conclusion: HNC cells variably express TLR8 protein, and engagement of TLR8 signaling with a pharmacological agonist VTX-2337 potently induced autophagy in cancer cells. VTX-2337 increased cancer cell sensitivity to cetuximab and potently inhibited HNC cell proliferation. Given the published ability of VTX-2337 to enhance Ab-mediated NK cell lysis, combinatorial strategies would appear promising.